A high-quality genome of Actinidia eriantha provides new insight into ascorbic acid regulation - Guang-lian LIAO; Chun-hui HUANG; Dong-feng JIA; Min ZHONG; Jun-jie TAO; Xue-yan QU; Xiao-biao XU (Journal of Integrative Agriculture)
Actinidia eriantha is one of the species of kiwifruit with a particularly high ascorbic acid (AsA) content. However, the molecular mechanism driving AsA richness in fruit remains unclear. In order to reveal the molecular mechanism of AsA richness in A. eriantha, this study constructed a regulatory network related to AsA metabolism by combining genomics, metabolomics and transcriptomics. We assembled a high-quality genome of A. eriantha ‘Ganlv 1’ with only five remaining gaps. The assembly is comprised of 29 pseudochromosomes with a total size of 615.95 Mb, and contig N50 of 20.35 Mb. Among them, 24 of the pseudochromosomes were obtained directly from telomere-to-telomere. The LTR assembly index score and consensus quality value were 21.34 and 39.90%, respectively. Subsequently, 61 metabolites and 2 092 genes were found to be differentially accumulated/expressed during fruit development by metabolome and transcriptome assays, respectively. AsA metabolism and the cyclic regeneration pathway were found to have high expression levels throughout fruit growth and development, suggesting its crucial role in the regulation of AsA. Furthermore, the AsA contents are highly associated with ascorbate peroxidase genes. The genome obtained in this study provides genomic resources for the genetic and breeding research of A. eriantha, and the constructed regulatory network can provide a public data platform for future research on kiwifruit.